Antibacterial activity of bark fungal endophytes from Aquilaria malaccensis Lam. - Mascariñas, Rian Lorenzo V.; Fuentes, Rolly G. (2024)
Aquilaria malaccensis is a tree native to the Philippines, which is economically important for its production of agarwood, a fragrant resinous product used in traditional medicine and in perfume production. Fungal endophytes from Aquilaria species have been widely studied as a source of bioactive compounds with potential antibacterial properties. In this study, 26 fungal endophytes were isolated and identified from two A. malaccensis hosts, a healthy and infected (inoculated) tree, from Leyte and their antibacterial activities were studied. The agar plug diffusion assay was performed as a preliminary screening method for the antibacterial activity of the isolates against Staphylococcus aureus. Bacillus cereus, Escherichia coli, and Pseudomonas aeruginosa. Active endophytes were then mass produced through submerged liquid fermentation and their secondary metabolites were extracted with ethyl acetate (EtOAc). The antibacterial activity of their crude EtOAc extracts were then tested with the Kirby-Bauer Disk Diffusion Assay and microbroth dilution assay. In addition, thin layer chromatography (TLC) characterization was performed for preliminary characterization of the crude EtOAc extract of the most active isolate. Results of the antibacterial assays revealed that P. citrinum isolated from the infected (inoculated) A. malaccensis exhibited the highest antibacterial activity against S. aureus among the isolates with an MIC of 2.5 mg/mL. Additionally, TLC characterization showed that the P. citrinum crude EtOAc extract contains phenols, flavonoids, steroids, and triterpenes which may have contributed to its antibacterial activity. This study introduces A. malaccensis as a potential host for fungal endophytes which are promising sources of antibacterial compounds that can be explored for their pharmaceutical applications.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.